Plastik Sanatlar Alanında Resim Sanatçı Seçkileri-1 - Keleş, Nurgül; Alioğlu, Hamid Maharramov; Erol, Songül Esin; Özmen, Ahmet Fatih; Eren, Abdurrahman; Sevindik, İlyas; Gezen, Mehmet Cihan; Özçelikçi Taşören, Birgül; Büyükparmaksız, Mehmet Ali (2024)
-